Peixes marinhos e estuarinos do Ceará e seu estado de conservação - Souza, Lilian Glória Xavier de (2022)
The marine and estuarine ichthyofauna from the State of Ceará was listed in the present study. The fish species, they were compiled from three sources: (1) recovery and identification of fish from the Ichthyological Collections Dias da ROCHA – CIDRO A e B (2) consult national and international natural collections from online database and (3) systematic review of scientific literature. The state of Ceará has a total of at least 408 species of marine and brackish fish. The conservation status of the species was compiled from two red lists: International Union of Conservation of Nature - IUCN (global) and Ministry of Environment - MMA (national). Altogether, forty-six (46) species fall into one of the three threat categories (“Vulnerable”, “Endangered” and “Critically endangered”). The most threatened taxonomic group is Elasmobranchii (sharks and rays).